Albumin as a prognostic factor in the survival of patients with diffuse large B-cell lymphoma treated at a hospital in Lima, Peru - Morales-Cuzquén , Luis Gustavo (2024)
Introduction: Diffuse large B-cell lymphoma (DLBCL) is the most prevalent form of non-Hodgkin lymphoma in adults, with a high mortality rate. Low serum albumin can be a biological indicator of the disease reflected as increased inflammation or increased toxicities. Currently, the International Prognostic Index (IPI) is the accepted model for prognosis in patients with DLBCL. Objective: To determine the prognostic value of albumin in overall survival (OS) of patients with DLBCL treated with immunochemotherapy in a hospital in Peru during the period 2017-2019. Materials and methods: Analytical, cross-sectional, retrospective and observational study. It consisted of 161 patients with DLBCL diagnosed and treated during the mentioned period. The SPSS v27 program was used for statistical analysis. Hazard ratios (HR) and 95% confidence intervals (CI) were used to assess the prognostic impact of albumin on overall survival (OS). Results: The OS of patients up to 12 months was 94%, 3 years was 87%, and 5 years was 87%. In multivariate Cox proportional hazards regression analysis, albumin (p=0.037; HR=3.614 95% CI [1.079 – 12.105]) and IPI (p=0.017; HR 1.891 95% CI [1.121 – 3.19]) were found to be the independent variables influencing OS in patients with DLBCL. Conclusions: Hypoalbuminemia might be a risk factor for shorter OS. In association with the IPI, a cumulative prognostic scoring system could be developed in patients with DLBCL.